AB0082 New insights to the pathogenesis of two orphan anca[-] vasculitides: childhood polyarteritis nodosa and behÇet disease. (23rd January 2014) - Batu, E.D.; Taskıran, E.Z.; Kilic, L.; Akdogan, A.; Yilmaz, E.; Ozen, S.
Abstract : Background: Vasculitides are characterized by inflammation of the vessel wall. However, we still do not know the pathogenesis of the inflammation and why they affect the target organs that they do. Objectives: The aim of this study was to study the role of TNF-α, MMP9 and the balance between Th17 and Tregs in two vasculitides, polyarteritis nodosa and Behçet disease. Methods: The study group included four patients with childhood PAN who met the classification criteria suggested by Ankara 2008, PReS/Pr into/EULAR endorsed criteria [1], the four BD vasculitis patients met the Lancet criteria [2]. Blood was drawn while all patients had active disease. The control group consisted of 3 healthy individuals with a median age of 20 who were bled for routine pre-operative work. The expression levels of FOXP3, IL-17, MMP9, TNF-α in PBLs were analyzed using qRT-PCR in patients and normal controls. Results: IL-17, MMP9, TNF-α expressions were significantly increased compared to normal controls (p=0.0308, p=0.0022, and p=0.0127 respectively). There was no difference in the expression for FoxP3. Conclusions: TNF-α, a cytokine with immunomodulatory effect, has been implicated in the pathogenesis of many vasculitides. Our results implicating both TNF-α and MMP9 in the pathogenesis of PAN and BD, may provide support for the use of anti-TNF-α. Increased levels of MMPs have been reported in other common vasculitides such as Kawasaki disease [3] and HSP [4]. The increased expression of MMP9 among our patients highlights its role in both PAN and BD. Th17 cells, a distinct subtype of T-helpers, are considered to take a major role in the pathogenesis of autoimmune and chronic inflammatory disorders [5]. In a recent GWAS, IL-23/IL-17 axis has been identified as a disease susceptibility locus in BD [6]. Our study supports that Th17 cells seem to be operative in both of BD and PAN. Understanding the inflammatory pathway may lead us to design more specific treatment. These results suggest that TNF-α, MMP9, and IL-17 may indeed be potential targets for therapy in these troublesome diseases. References: Ozen S, Pistorio A, Iusan SM, et al; Paediatric Rheumatology International Trials Organisation (PRINTO). EULAR/PRINTO/PRES criteria for Henoch Schönlein purpura, childhood polyarteritis nodosa, childhood Wegener granulomatosis and childhood Takayasu arteritis: Ankara 2008. Part II: Final classification criteria. Ann Rheum Dis 2010;69(5):798-806. Criteria for diagnosis of Behçet's disease. International Study Group for Behçet's Disease. Lancet 1990;335:1078-80. Senzaki H, Masutani S, Kobayashi J, et al. Circulating matrix metalloproteinases and their inhibitors in patients with Kawasaki disease. Circulation 2001;104:860-863. Majahan N, Bisht D, Dhawan V, et al. Transcriptional expression and gelatinolytic activity of matrix metalloproteinases in Henoch-Schonlein purpura. Acta Paediatrica 2010;99:1248-1252. Annunziato F, Cosmi L, Liotta F, et al. Type 17 T helper cells-origins, features and possible roles in rheumatic disease. Nat Rev Rheumatol 2009;5:325-331. Mizuki N, Meguro A, Ota M, et al. Genome-wide association studies identify IL23R-IL12RB2 and IL10 as Behcet's disease susceptibility loci. Nat Genet 2010;42(8):703-706. Disclosure of Interest: None Declared